A seven-bend-achromat lattice option for the HALF storage ring. (4th January 2022) - Xu, J.; Ren, Z.; Yang, P.; Liu, G.; Bai, Z.
Abstract: The Hefei Advanced Light Facility (HALF) is a soft X-ray diffraction-limited storage ring being designed with an energy of about 2.2 GeV and an emittance goal of less than 100 pm·rad. The present HALF lattice is a modified hybrid six-bend-achromat (6BA) lattice with a long and a short straight section in each cell. In this paper, a 7BA lattice is designed for HALF as a promising option, which follows the main feature of hybrid 7BA lattice, but to have a compact configuration and lower emittance, all bends in this lattice are combined-function bends and reverse bends. The designed HALF storage ring has a circumference of 388.8 m and 20 identical cells. Two solutions with different betatron tunes are studied for this lattice. One with smaller tunes has better nonlinear dynamics performance allowing for off-axis injection, which has a natural emittance of 67 pm·rad. The other with larger tunes has very small beta functions at the straight section as well as lower natural emittance of 59 pm·rad, which can enhance the brightness of insertion device (ID) radiation. The intra-beam scattering effect and ID radiation properties are also presented in this paper.